Copyright in the Digital World: Identifying and Analysing Spaces for Harmonisation in the Pacific Alliance Trade Bloc - Rogaler, Tomas Andrés (Latin American Journal of Trade Policy, 2025)
Digital trade has been driven by the technological revolution and the universalisation of the Internet, redefining both consumption and the structure of international trade. Despite its potential benefits, the digital transformation has brought with it increasing regulatory complexity, which is implemented heterogeneously by states. A crucial aspect in this context is copyright protection, which is fundamental to stimulating creativity and innovation. This study analyses the provisions on the protection of copyright in the digital environment that the members of the Pacific Alliance (PA) have implemented in their preferential trade agreements with other states and examines the similarity between them. The study places special emphasis on how this similarity could influence the trade flow of digital services and the potential regulatory harmonisation among PA members. It is expected that the results will contribute to a better understanding of copyright regulation in the digital world and will serve as a basis for the formulation of more cohesive and effective policies for the benefit of the PA.